Self-efficacy and Job Stress among Tobacco Farmers - Enggal Hadi Kurniyawan; Alfia Andriyani; Emi Wuri Wuriyaningsih; Erti Ikhtiarini Dewi; Rismawan Adi Yunanto; Fitrio Deviantony; Yeni Fitria (KHD Production, 2023)
Farmers have heavy work demands, so farmers are at risk of injury and work-related illnesses such as mental stress disorder. This study analyzed the relationship between self-efficacy and work stress in tobacco farmers. The research design used is the analytic correlation with a cross-sectional approach. The sampling technique uses probability sampling with cluster sampling. The sample for this research is tobacco farmers who are members of the farmers' group, with a sample size of 100 respondents. The instrument used in this study was the GSE (General Self-efficacy) Questionnaire to measure self-efficacy in tobacco farmers. The DASS 42 Questionnaire (Depression, Anxiety, Stress, Scale) was used to measure work stress—data analysis using the Pearson test correlation test. The average tobacco farmer has high Self-Efficacy and low work stress. The results of the Pearson test, namely the p-value of 0.001 with a correlation value of -0.419, show a relationship between self-efficacy and work stress with a moderate correlation level with a negative correlation direction. Nurses are expected to carry out counseling activities for tobacco farmers to prevent work stress and increase self-efficacy in tobacco farmers.